Cities, peasants, and food in classical antiquity essays in social and economic history - Garnsey, Peter 1938- (Cambridge Univ. Press, 1998)
Sixteen essays in the social and economic history of the ancient world, by a leading historian of classical antiquity, are here brought conveniently together. Three overlapping parts deal with the urban economy and society, peasants and the rural economy, and food-supply and food-crisis. While focusing on eleven centuries of antiquity from archaic Greece to late imperial Rome, the essays include theoretical and comparative analyses of food-crisis and pastoralism, and an interdisciplinary study of the health status of the people of Rome using physical anthropology and nutritional science. A variety of subjects are treated, from the misconduct of a builders' association in late antique Sardis, to a survey of the cultural associations and physiological effects of the broad bean
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Erscheinungsjahr des E-Books: 2009
Keywords: Geschichte 450 v. Chr.-200 v. Chr.; Sozialgeschichte; Geschichte 100 v. Chr.-500; Geschichte; Stadt; Cities and towns / Rome; Peasants / Rome; Food supply / Rome; Food supply / Greece / History / To 1500; Ernährung; Antike; Bauer; Lebensmittelversorgung; Stadtwirtschaft; Landwirtschaft; Griechenland; Rom; Römisches Reich; Griechenland -- Altertum; Aufsatzsammlung